Correlation of HPV-DNA Test with Cytology and Histology for the Diagnosis of Cervical Cancer and Precancerous Lesions in a Tertiary Care Hospital in Bangladesh (Journal of Armed Forces Medical College, Bangladesh, 2017)
Introduction: Cervical cancer is the second most prevalent cancer among women worldwide. High-Risk Human Papilloma virus (hr-HPV) is an established cause of cervical cancer and precancerous lesion. Studies have shown the relationship between the HPV-DNA test with cervical precancerous and cancerous lesion in diagnosing cervical cancer. This study aimed to correlate HPV-DNA test with both cytology and histology.Objective: To find out the correlation of HPV-DNA test with cytology and histology for the diagnosis of cervical precancerous and cancerous lesion.Materials and Methods: Cervical smears and DNA samples were collected from the selected patients attending the colposcopy clinic of Bangabandhu Sheikh Mujib Medical University (BSMMU) from July 2011 to April 2013. Biopsy was done on colposcopically positive cases and histopathology reports were obtained. Thus 99 histologically proven patients of cervical cancer and precancerous lesion were selected. Pap smear was carried out on these 99 patients. HPV-DNA test (Hybrid Capture-2 assay) was carried out on the same samples and viral loads were estimated.Results: Among the 99 cases, 28(28.28%) cases were positive with Hybrid Capture-2(HC-2) assay. Out of 60 cases of CIN-I (Cervical Intraepithelial Neoplasia-1), 7(11.7%) cases were positive with HC-2. Among others, 3(15.0%) cases of CIN-II were positive with HC-2. The viral load was very high in invasive SCC (squamous cell carcinoma) cases in contrast to other categories of histological and cytological diagnosis. A significant relationship was observed between HC-2 and histological diagnosis (P